Utilização e verificação do código GEANT4 em aplicações médicas: estudo de caso para elétrons - Sandro Roger Boschetti (2013)
The increase ever accelerating of the use of ionizing radiation in several sectors of medicine is a reality. In this sense, codes inspired in the Monte Carlo method have been developed and adapted to meet the growing demand of the ionizing radiation application in medical utilizations. Among the most frequently used codes for radiation transport is included the GEometry ANd Tracking 4 (GEANT4) provided by Conseil Européen pour la Recherche Nucléaire (CERN). The GEANT4 is a set of software tools named toolkit. The code uses object oriented programming in C++ and it is currently used in several areas with wide range of energy. Several physical processes and particles have been incorporated intothe GEANT4 toolkit allowing its use in medical physics. This work presents a methodology for installing and using the GEANT4 code as well as to perform its verification for some applications with electons in order to stimulate its use, improve the code and increase its number of users.